Technology and/or nature: denatured/renatured/engineered/artifacted life? - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 2016)
In our high-tech world, do we live at the end of nature? Is the technosphere replacing the biosphere? Can humans control their genetically inherited Pleistocene appetites in an Anthropocene Epoch? Is experience of the urban, rural, and wild a three-dimensional life, with life focused on fewer dimensions under-privileged? Do we, ought we, wish to live on an engineered planet? Would this fulfill human destiny or display human arrogance, failing to embrace our home planet in care and wonder? True, we must become civilized. Be a resident on your landscape. True, the future holds advancing technology. But equally: we do not want to live a denatured life, on a denatured planet.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: technology; nature; technosphere; biosphere; human nature; human genes; managing Earth; geoengineering; home planet; denatured life; denatured planet; Anthropocene Epoch